(3GdeSDhdjI GdOSJhQjI hGdbGfhfjI ddOhdI aj eLGd GdQYGjI GdUMjI (B:s (3OQGSI ebGQfI (B/ s - (3fha eMeO NGdO eTYGf GdagO GdeTYGf,s; (3LGHQ LGO fUGQ,s; (3LGeYI GdbGgQI s ((3GdbGgQI s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI , s, 2023)
(3Ef ef Mb GdEfSGf Cf jMjG MjGI EfSGfjI jJeJY ajgG HeLehYI ef GdMbhb GdCSGSjI GddUjbI HUaJg cEfSGf , hGdUMI JeKd ecGfI YGdjI aj MjGI GdHTQ , hJYJHQ ef Cge Mbhb GdEfSGf hCYdGgG bOQkG hCHQRgG ecGfkI , hQHeG jJhba YdjgG MjGI GdEfSGf cdgG (B. (3hMbhb GdEfSGf HUaI YGeI dgG LPhQ VGQHI aj GdJGQjN hdbO YdJ CUhGJ GdabgGA hGdegJejf HMbhb GdEfSGf hYbOJ GdeDJeQGJ hUjZJ GdEYdGfGJ hGdGJaGbjGJ GdJj JJQLe gPg GdMbhb , hUjZJ GdMbhb GdeOfjI hGdSjGSjI cLjd Chd ef Mbhb GdEfSGf , Ke JdGgG GdLjd GdKGfj hgj GdMbhb GdGLJeGYjI hGdGbJUGOjI hef HjfgG GdMb aj GdQYGjI GdUMjI (B. (3hEf CcKQ eG jge GdaQO gh Cf jchf eJeJYkG HMbhbg , hjfHZj Cf jecf efgG hgfGc Mbhb jMJGL ajgG Edi eYGhfI GdOhdI cj jMUd YdjgG , adG jSJWjY GdaQO Cf jefY eSHHGJ GdeQV hJgjFI CSHGH GdUMI GdYGeI GdJj JTed GdMaGX Ydi GdHjFI Hcd YfGUQgG hZjQ Pdc ef QhGaO GdJdhK , ceG dG jSJWjY aj GdZGdH GdCYe QO ZGFdI GdeQV ef eGdg GdNGU , hef gfG HQRJ eSFhdjI GdOhdI aj caGdI GdMb aj GdQYGjI GdUMjI hGdUMI GdYGeI (B. (3hERGA GgJeGe GdehGKjb GdOhdjI hef bHdgG GdTQjYI GdESdGejI HgPG GdMb ade jYO ebHhdkG UOhQ OSJhQ aj Cj OhdI MOjKI ef Ohf Cf jJVef GdMbhb GdCSGSjI ddCaQGO hef HjfgG GdMb eMd GdOQGSI , EP Cf JfXje GdMb Yf WQjb GdOSJhQ jVef dg GdKHGJ hGdGSJbQGQ , hjTYQ GdeTQY HSeh gPG GdMb hJcQjSg ef bHd GdhKjbI GdbGfhfjI (B. s
A person has the right to live a human life in which he enjoys a set of basic rights attached to his capacity as a human being, and health represents a high position in human life, and it is considered one of the most important human rights and the highest value and most prominent status, and perhaps the whole life of a person depends on it. Human rights in general have deep roots in history. The voices of jurists and those interested in human rights have been raised. Conferences have been held and declarations and agreements that translate these rights have been formulated. Civil and political rights have been formulated as a first generation of human rights, then followed by the second generation, which are social and economic rights, including the right to health care. . What matters most to the individual is that he enjoys his rights, and he should be able to enjoy them, and there are rights in which he needs the help of the state in order to obtain them. The individual cannot prevent the causes of disease and create the causes of public health that include preserving the environment with all its elements and other tributaries of pollution. In most cases, he cannot repay the disease from his own money, hence the responsibility of the state to ensure the right to health care and public health. And in light of the interest of international covenants, and before them, Islamic law, in this right, it is no longer acceptable to issue a constitution in any modern country without including the basic rights of individuals, including the right under study, as organizing the right through the constitution guarantees stability and stability for it, and the legislator feels the supremacy and consecration of this right. by legal document.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2023. s
(3HHdjhLQGajG(B: (3UaMGJ (B564-596.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdQYGjI GdUMjIs; (3GdQYGjI GdUMjIs -- (3bhGfjf h JTQjYGJs; (3GdMbhb GdeOfjI hGdSjGSjIs -- (3GdMb aj GdQYGjI GdUMjIs -- (3eSHHGJ GdeQV hJgjFI CSHGH GdUMI GdYGeIs